Lamb waves manipulation by piezoelectric metasurface with tunable diffraction orders - Shao, Shixuan; Chen, Jiyue; Xia, Rongyu; Li, Zheng (Frontiers in Physics, 2023)
In this paper, a piezoelectric metasurface is proposed to manipulate the anti-symmetric mode Lamb wave by altering the diffraction order. The metasurface attached to a host plate is symmetrically arranged by out-of-plane polarized piezoelectric patches connected with synthetic inductance circuits. Without changing the physical configuration, the transmitted phase of the anti-symmetric mode Lamb wave can be shifted arbitrarily in 0 ∼ 2π range by the metasurface. Furthermore, the relationship between the phase gradient and diffraction order is investigated, and different orders of diffraction waves can be obtained by adjusting the shunting inductance circuits. The symmetric transmission and asymmetric transmission from a couple of axis symmetric incident waves can be realized by utilizing +1st-order and −1st-order diffraction. Moreover, omnidirectional wave reflection and wave trapping in channelized waveguides can also be realized by utilizing the 0th-order diffraction. The results indicate that the proposed piezoelectric metasurface has great potentials in manipulating guided waves with a large incident angle and isolating wave propagation.